2007
DOI: 10.1103/physrevlett.98.021101
|View full text |Cite
|
Sign up to set email alerts
|

Tests of the Gravitational Inverse-Square Law below the Dark-Energy Length Scale

Abstract: We conducted three torsion-balance experiments to test the gravitational inverse-square law at separations between 9.53 mm and 55 µm, probing distances less than the dark-energy length scale λ d = 4 hc/ρ d ≈ 85 µm. We find with 95% confidence that the inverse-square law holds (|α| ≤ 1) down to a length scale λ = 56 µm and that an extra dimension must have a size R ≤ 44 µm.PACS numbers: 95.36.+x,04.80.Cc,12.38.Qk Recent cosmological observations [1,2,3] have shown that 70% of all the mass and energy of the U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
981
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 935 publications
(1,016 citation statements)
references
References 17 publications
32
981
2
1
Order By: Relevance
“…At short distances, recent torsion balance experiments [15] have found that Newton's Inverse Square Law (ISL) holds down to a length scale of 56 µm. This result is especially interesting because this length is less than the dark-energy length scale λ = (hc/ρ vac ) 1 4 ∼ 85µm corresponding to energy density ρ vac ∼ 3.8 keV/cm 3 (or (0.002 eV) 4 ) extracted from dark energy astrophysics experiments.…”
Section: Tests Of General Relativitymentioning
confidence: 99%
“…At short distances, recent torsion balance experiments [15] have found that Newton's Inverse Square Law (ISL) holds down to a length scale of 56 µm. This result is especially interesting because this length is less than the dark-energy length scale λ = (hc/ρ vac ) 1 4 ∼ 85µm corresponding to energy density ρ vac ∼ 3.8 keV/cm 3 (or (0.002 eV) 4 ) extracted from dark energy astrophysics experiments.…”
Section: Tests Of General Relativitymentioning
confidence: 99%
“…That is a very interesting relation from the perspective of the hierarchy problem, because it allows for the effective mass M 4 that we observe to be huge even when the true mass M 4+n is not that big. Just to put some numbers, let us consider r c 1 µm ⇒ (r c ) −1 0.18 eV , which is just below the lower bound for the experimental validity of newtonian gravitation [10]. This automatically gives the following values for M 4+n…”
Section: The Hierarchy Problemmentioning
confidence: 99%
“…Also, since we obtained the deviation from Newton's 2nd law for free particle constrained to the surface of a 3-torus, relation (3.48), any test of the gravitational inverse-square law can be used to investigate our model [86,87]. For instance, to observe the transition from inverse-square law of Newtonian gravitation imposed via extra dimensions in brane world models, some measurements such as submillimeter measurement of gravity are proposed and can be used to test our model [71,[88][89][90][91].…”
Section: Jhep01(2018)017mentioning
confidence: 99%